Pelatihan Manajemen Operasional Produk dan Legalitas Usaha Bagi Ibu-Ibu PKK Asman Kelasi Di Wisata Kampung Kelengkeng Kabupaten Sidoarjo - Nekky Rahmiyati; Febby Rahmatullah Masruchin; Bella Aureliya E Sc; Sabrina Ayu Rizkya; Annisa Beauty Ananda; Fahmi Muhammad; Rendy Achmad Wahyu (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
The purpose of this activity is to help startup business actors to increase their economic productivity, Untag Surabaya through the Matching Fund program seeks to connect the world of education and the business world, namely making real efforts to equip new business actors in preparing themselves to enter the business world so as to help business actors. Beginners to increase their economic productivity so that they become reliable business actors, one of the matching fund activities is to improve the quality of human resources for PKK women, Asman Kelasi in Kelengkeng Village Tourism, Simoketawang Village, Wonoayu District, Sidoarjo Regency. The method of implementing this activity is carried out collaboratively between the Matching Fund program implementers, the Community Empowerment & Village Development Agency, and is divided into three stages, namely, preliminary surveys, training and mentoring with the target of Ms. PKK Asman Kelasi who is a business actor. The results of the activities include an increase in practical knowledge that is easy to apply in production and operations, in this training participants understand more about how to plan the output of a production and production management and business legality. In addition, there has been capacity building for business actors, who initially did not have an NIB after training and mentoring by successfully managing a Business Identification Number (NIB), which is an identity belonging to a business actor issued directly by OSS or Online Single Submission. Partners showed great enthusiasm and enthusiasm in supporting the longan tourism village and participated in this training, as demonstrated by the success of NIB management.